Synthesis of novel inhibitors of 1-Deoxy-D-xylulose-5-phosphate reductoisomerase as potential anti-malarial lead compounds - Mutorwa, Marius Kudumo (Rhodes University, Faculty of Science, Department of Chemistry, 2011)
This research has focused on the development of novel substrate mimics as potential DXR inhibitors of 1-deoxy-D-xylulose-5-phosphate reductoisomerase (DXR), an essential enzyme in the mevalonate-independent pathway for the biosynthesis of isoprenoids in Plasmodium falciparum. DXR mediates the isomerisation and reduction of 1-deoxy-D-xylulose-5-phosphate (DOXP) into 2C-methyl-D-erithrytol 4-phosphate (MEP) and has been validated as an attractive target for the development of novel anti-malarial chemotherapeutic agents. Reaction of various amines with specially prepared 4-phosphonated crotonic acid in the presence of the peptide coupling reagent, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC), has afforded a series of amido-phosphonate esters in moderate to good yields (48% - 73%) which, using a RuCl₃/CeCl₃/NaIO₄ catalyst system, have been dihydroxylated to furnish the dihydroxy-amido phosphonate ester pro-drugs; subsequent hydrolysis under microwave irradiation has afforded the corresponding phosphonic acids. A second series of potential inhibitors viz., 3-substituted aniline-derived phosphonate esters, their corresponding phosphonic acids and mono-sodium salts, have also been successfully synthesised. In these compounds, the essential functional groups are separated by one, two, three or four methylene groups, Deprotonation of the 3-substituted aniline substrates, followed by reaction with the appropriate ω-chloroalkanoyl chloride produced the ω-chloroamide intermediates, which were subjected to the Michaelis-Arbuzov reaction to afford the diethyl phosphonate esters in moderate to good yields (48% - 74%). Microwave-assisted TMSBrmediated cleavage of the phosphonate esters furnished the phosphonic acids, neutralisation of which afforded the mono-sodium salts. Furan-derived phosphate esters and phosphonic acids have been prepared as conformationally-restricted DOXP analogues. Functionalization at C-5 of the trityl-protected furan was achieved using the Vilsmeier-Haack formylation and Friedel-Crafts acylation reactions and, following de-tritylation, phosphorylation and oximation, using hydroxylamine hydrochloride, the novel oxime derivatives have been isolated as a third series of potential DXR inhibitors in very good yields (87% - 96%). Finally, in order to exploit an additional binding pocket in the PƒDXR active site, a series of N-benzylated phosphoramidic derivatives were obtained in seven steps from the starting material, diethyl phosphoramidate. The known inhibitors, fosmidomycin and its acetyl derivative FR900098, were also successfully synthesised as standards for STD-NMR binding and inhibition assays. In all, over 200 compounds (136 novel) have been prepared and appropriately characterised using 1-and 2-D NMR and IR spectroscopic analysis and, where necessary, HRMS or combustion analysis. Saturation Transfer Difference (STD) protein-NMR experiments, undertaken using selected compounds, have revealed binding of most of the ligands examined to EcDXR. Computersimulated docking studies have also been used to explore the preferred ligand-binding conformations and interactions between the ligands and essential DXR active-site residues, while DXR-enzyme inhibition assays of selected synthesised ligands have revealed certain patterns of inhibitory activity.
Keywords: Antimalarials -- Development; Plasmodium falciparum; Malaria -- Chemotherapy; Drug development; Lead compounds; Phosphonates; Phosphonic acids; Ligands